Ion beam irradiation of ABO4 compounds with the fergusonite, monazite, scheelite, and zircon structures. Issue 10 (7th July 2020) - de los Reyes, Massey; Aughterson, Robert D.; Gregg, Daniel J.; Middleburgh, Simon C.; Zaluzec, Nestor J.; Huai, Ping; Ren, Cuilan; Lumpkin, Gregory R.
Abstract: The effects of irradiation on CaWO4, SrWO4, BaWO4, YVO4, LaVO4, YNbO4, and LaNbO4 were investigated on thin crystals using 1.0 MeV Kr ions at 50‐1000 K. All of the ABO4 compounds can be amorphized with calculated damage cross sections ( σa  = 1/ F c0 ) in the range of ~0.30‐1.09 × 10 ‐14 cm 2 ion −1 at zero Kelvin. The analysis of fluence‐temperature data returned critical temperatures for amorphization ( T c ) of 311 ± 1, 358 ± 90, 325 ± 19, 415 ± 17, 541 ± 6, 636 ± 26, and 1012 ± 1 K, respectively, for the compounds listed above. Compared with previous in situ irradiation of ABO4 orthophosphate samples using 0.8 MeV Kr ions, the T c values of LaVO4 and YVO4 are higher than those of LaPO4 and YPO4 by 82 K and 124 K, respectively. The T c values of the three scheelite structures, CaWO4, SrWO4, and BaWO4, indicate that they are the most radiation tolerant compounds under these conditions. The A‐B cation anti‐site energies, Ef AB, determined by DFT range from 2.48 to 10.58 eV and are highly correlated with the A‐B cation ionic radius ratio, r A / r B, but are not correlated with T c across the different structure types, suggesting that the formation and migration energies of Frenkel defects play a more important role in damage recovery in these compounds. We also discuss the role of cation and anion charge/iconicity as determined by DFT. ABO4 compounds with the zircon structure and B = P or V have a distinct advantage over those with B = Si as the damaged regions do not appear to be significantly affected by polymerization of (PO4 ) 3− or (VO4 ) 3− groups which might stabilize the amorphous fraction and ultimately lead to phase separation as observed in zircon (ZrSiO4 ).